(untitled) (Research, Society and Development, 2022)
In Brazil, breast cancer has a higher incidence in women aged 40 to 59 years and is associated with several risk factors, including: genetic, environmental and behavioral factors. It is characterized by disordered proliferation and constant cell growth of cells. Among the most effective forms of early detection are clinical breast examination and mammography. Breast imaging tests, such as mammography, and depending on the situation, ultrasound or MRI are important for diagnosis. The general objective of this work is to describe aspects related to breast cancer diagnosis methods in Brazil. This study consists of developing a systematic review. Regarding the methodology, we will use the recommendations of the PRISMA method. A bibliographic survey of productions indexed in the following electronic databases was carried out: Scientific Electronic Library Online (SCIELO), VHL and PubMed, in the languages: English, Portuguese and Spanish. Having selected 10 studies for analysis, these demonstrate that a correlation of conditions between late diagnosis and the socioeconomic level of the woman, as well as that when suspecting breast cancer during a screening mammogram or during palpation of the breasts. The diagnosis must be confirmed by complementary exams. The highest mortality of women with breast cancer occurs in places where socioeconomic factors are more precarious, factors that are aggravated by the poor distribution of resources that negatively influence the identification and early treatment of breast cancer.